Elastic Properties And Ionic Conductivity Of Lithium Phosphate And Lithium Borate Glasses - Low, Yee san (1999)

(untitled)
Glasses are of scientific interest because their compositions can be varied over a very wide range and it is possible to produce glasses for a particular application. In this work, lithium glasses with phosphate and borate as the glass formers are studied. Four series of lithium glasses, lithium phosphate (Li2O)x(P2O5)1-x (x = 0.10 to 0.50), lithium chlorophosphate (LiC1)y[(Li2O)0.4(P2O5)0.6]1-y(y=0.10 to 0.50).lithium borate (Li2O)x(B2O3)1-x(X= 0.15 to 0.40) and lithium chloroborate (LiCI)y[(Li2O)o.25(B2O3)o.75]1-y (y = 0.05 to 0.25) glasses have been prepared for the elastic property and ionic conductivity measurement using the rapid quenching technique. The ultrasonic velocities of the glass samples were measured by using the MBS 8000 ultrasonic data acquisition